2004
DOI: 10.1016/s0736-0266(03)00165-7
|View full text |Cite
|
Sign up to set email alerts
|

Induced membranes secrete growth factors including vascular and osteoinductive factors and could stimulate bone regeneration

Abstract: Based on a new concept, a procedure combining induced membranes and cancellous autografts allows the reconstruction of wide diaphyseal defects. In the first stage of this procedure, a cement spacer is inserted into the defect; the spacer is responsible for the formation of a pseudo-synovial membrane. In the second stage, the defect is reconstructed two months later by an autologous cancellous bone graft. The aim of this study was to evaluate the histological and biochemical characteristics of these membranes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
358
2
37

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 515 publications
(407 citation statements)
references
References 25 publications
10
358
2
37
Order By: Relevance
“…High concentration rates of growth factors have been found in the membrane's cells, especially transforming growth factor b (TGFb), vascular endothelial growth factor (VEGF), and specific bone growth factors such as BMP-2. The membrane promotes human mesenchymal cell proliferation and differentiation into bone-forming cells [26]. In addition to this biological function, the induced membrane also prevents soft tissue protrusion in the defect, retains the bone graft in place and protects it against resorption, thus creating a favorable environment for bone engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…High concentration rates of growth factors have been found in the membrane's cells, especially transforming growth factor b (TGFb), vascular endothelial growth factor (VEGF), and specific bone growth factors such as BMP-2. The membrane promotes human mesenchymal cell proliferation and differentiation into bone-forming cells [26]. In addition to this biological function, the induced membrane also prevents soft tissue protrusion in the defect, retains the bone graft in place and protects it against resorption, thus creating a favorable environment for bone engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…Histological studies on rabbits demonstrated extensive Implementation of the Masquelet Technique in Complicated Septic Non-union of the Ulna-A case Report 296 neovascularisation in the bone defect, whereas immunohistochemical studies denoted production of growth hormones (VEGF,TGF-b1) in a time period of two weeks, as well as the osteoinductive growth hormone BMP-2 (bone morphogenetic protein 2), with peak output at 9 weeks [3,[5][6][7][8][9][10]. These molecules are vital to bone formation, metabolism and remodelling [6]. The interior part of this "pseudomembrane" imitates epithelium and the exterior part includes fibroblasts, myoblasts and collagen [4].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies show the membrane is richly vascularized by numerous small capillaries and with high concentrations of growth factors (vascular endothelial growth factor, transforming growth factor-b1), osteoblast precursors (CBFA1+), and osteoinductive (bone morphogenetic protein-2) factors when compared with control subjects [17,18]. Moreover, the membrane induced by cement shows an absence of inflammatory cells [18], as opposed to membrane induced by silicone interposition [10] which may prevent deleterious graft resorption.…”
Section: Discussionmentioning
confidence: 99%